1991
DOI: 10.1093/oxfordjournals.aje.a116019
|View full text |Cite
|
Sign up to set email alerts
|

Interpartner Reliability of Reporting of Recent Sexual Behaviors

Abstract: Epidemiologic studies exploring risks for sexually transmitted diseases, including human immunodeficiency virus infection, typically rely on self-report of sexual behaviors. Estimates of the incidence and prevalence of sexual practices are important measures for assessment of behavioral interventions as well as for examining disease transmission. This study examined the degree of agreement within heterosexual couples reporting frequency and type of sexual behaviors, including condom use. Self-reports were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…The existing data on interpartner agreement shows variable findings related to the population and behaviors under investigation [6,[12][13][14][15][16][17][18][19][20]. Studies examining behaviors within the partnership (frequency of intercourse, condom use) for the purpose of examining the reliability of individual reports show good to excellent agreement among both homosexual and heterosexual couples [14 -20].…”
mentioning
confidence: 99%
“…The existing data on interpartner agreement shows variable findings related to the population and behaviors under investigation [6,[12][13][14][15][16][17][18][19][20]. Studies examining behaviors within the partnership (frequency of intercourse, condom use) for the purpose of examining the reliability of individual reports show good to excellent agreement among both homosexual and heterosexual couples [14 -20].…”
mentioning
confidence: 99%
“…Two US studies of heterosexual couples have also found close agreement between the independent responses of the 2 partners 21,22 .…”
Section: Accuracy Of Exposure Informationmentioning
confidence: 68%
“…Biological markers may be useful in small studies; condom sales surveillance can be used for ecologic studies; and large cohort studies attempt to correlate STD incidence data with condom use data 23 . Most researchers have used test± retest or inter-partner reliability as an indicator of validity 21,22,24 . Other studies indicate that the type of coital log used in our study does collect accurate data on sexual exposures 25 .…”
Section: Accuracy Of Exposure Informationmentioning
confidence: 99%
“…Our multivariate analysis, which accounted for these possibilities, showed that the partner specificity still held. Our definition of type of partner was driven by the results of qualitative work (Peto et al, 1992); it was equivalent to those given in some studies (Evans et aL, 1991;Smith, 1991), while others have used a classification exclusively based on objective parameters, such as the frequency of sexual activity and/or the length of the relationship (Catania et al, 1992b;Plitcha et al, 1992;Upchurch et al, 1991Upchurch et al, , 1992. Whatever the method used to define partner type, similar results have been found.…”
Section: Sexual Practicesmentioning
confidence: 70%